2020
DOI: 10.2298/hemind200329015s
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a novel perfusion bioreactor system in cancer research

Abstract: Development of drugs is a complex, time- and cost-consuming process due to the lack of standardized and reliable characterization techniques and models. Traditionally, drug screening is based on in vitro analysis using two-dimensional (2D) cell cultures followed by in vivo animal testing. Unfortunately, application of the obtained results to humans in about 90 % of cases fails. Therefore, it is important to develop and improve cell-based systems that can mimic the in vivo-like conditions to provide more reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…The extrusion process had several optimization steps in order to obtain sustainable, long-term 3D cell culture. Based on previously published data, we decided to mix 2% w/v sodium alginate solution with the cell suspension to obtain a final concentration of 1.5% w/v alginate [20]. Further, the transport of oxygen and nutrients by diffusion through alginate hydrogels is limited to 200 µm [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extrusion process had several optimization steps in order to obtain sustainable, long-term 3D cell culture. Based on previously published data, we decided to mix 2% w/v sodium alginate solution with the cell suspension to obtain a final concentration of 1.5% w/v alginate [20]. Further, the transport of oxygen and nutrients by diffusion through alginate hydrogels is limited to 200 µm [21].…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor in the optimization study is the initial number of cells used to obtain 3D cultures. Previous studies with alginate scaffolds reported initial inoculation numbers from 1 × 10 5 to 1 × 10 7 cells, depending on the experimental purposes [20,[23][24][25][26]. In our model system, we used three different inoculation densities of U87 cells (1 × 10 6 , 2 × 10 6, and 4 × 10 6 cells/mL alginate), and all of them gave rise to the 3D culture that preserved proliferative potential during 28 days.…”
Section: Discussionmentioning
confidence: 99%
“…The single-use perfusion bioreactor system "3D Perfuse" (Innovation Center of the Faculty of Technology and Metallurgy, Belgrade, Serbia) was used for cultivation of alginate microfibers with immobilized rat glioma C6 cells. As before, the system consisted of a chamber, two 3-way stopcocks, a medium reservoir and a silicone tubing loop serving for gas exchange [41]. In the present experimental setup 0.5 g of wet microfibers with immobilized rat glioma C6 cells, cultured statically for 8 days, was placed in the bioreactor chamber (0.8 cm inner diameter, 4 cm height) formed by a piece of silicone tubing and the system was filled with 15 cm 3 of the culture medium.…”
Section: Bioreactor Cultivation Of Microfibers With Immobilized C6 Cellsmentioning
confidence: 99%
“…Studies of novel macroporous, composite scaffolds based on gellan gum and bioactive glass particles have shown that the fluid flow in perfusion bioreactors significantly promoted formation of a mineral phase as compared to static conditions, which could be related to scaffold implantation in vascularized tissues [24]. Finally, an integrative approach to optimization of biomaterial properties and operating conditions in biomimetic bioreactors may provide tools for evaluation of new drugs and treatment procedures on 3D models of human tissues, as well as for development of personalized medical therapies, and thus contribute to decrease the level of needed animal experimentation [29].…”
Section: Research In the Field Of Biomaterials Sciencementioning
confidence: 99%